2009
DOI: 10.1093/ndt/gfp575
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage in chronic renal failure patients

Abstract: Genetic damage increases when renal function decreases, being maximum in haemodialysis patients. Although part of the observed damage can be attributed to the uraemic state itself, other individual genetic factors can influence a state of genomic instability responsible for the observed genomic damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 39 publications
3
35
2
1
Order By: Relevance
“…The observed genetic damage may also be contributed by increased serum creatinine levels (which were 2.5x higher). Stoyanova et al [32] had also observed a significant positive correlation between serum creatinine levels and genomic damage being substantiated by observations of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…The observed genetic damage may also be contributed by increased serum creatinine levels (which were 2.5x higher). Stoyanova et al [32] had also observed a significant positive correlation between serum creatinine levels and genomic damage being substantiated by observations of the present study.…”
Section: Discussionsupporting
confidence: 91%
“…DNA breaks present in peripheral blood lymphocytes were measured using the comet assay performed following the standard protocol, as previously described (Singh et al, 1988;Stoyanova et al, 2010) with minor modifications. Briefly, isolated lymphocytes from 2 mL of blood from each patient were cryopreserved until use, in 500 µL of medium containing 90% serum and 10% DMSO.…”
Section: Comet Assaymentioning
confidence: 99%
“…Several lines of evidence indicate that nucleic acid damage associated with oxidative stress increases in CKD and HD patients. Stoyanova et al [102] reported recently that oxidative nucleic acid damage was higher in HD ( n = 77) than in CKD patients ( n = 176). Another study reported that patients with CKD exhibit upregulation of a number of genes involved in the oxidative phosphorylation system, suggesting that an impaired mitochondrial respiratory system contributes to increased oxidative stress [103].…”
Section: Consequences Of Oxidative Stress and Oxidative Nucleic Acmentioning
confidence: 99%